Genetic and cellular evidence of decreased inflammation associated with reduced incidence of posttraumatic arthritis in MRL/MpJ mice. Issue 3 (25th February 2013) - Lewis, John S.; Furman, Bridgette D.; Zeitler, Evan; Huebner, Janet L.; Kraus, Virginia B.; Guilak, Farshid; Olson, Steven A.
Abstract Objective To examine the relationship between inflammation and posttraumatic arthritis (PTA) in a murine intraarticular fracture model. Methods Male C57BL/6 and MRL/MpJ "superhealer" mice received tibial plateau fractures using a previously established method. Mice were killed on day 0 (within 4 hours of fracture) and days 1, 3, 5, 7, 28, and 56 after fracture. Synovial tissue samples, obtained prior to fracture and on days 0, 1, 3, 5, and 7 after fracture, were examined by reverse transcription–polymerase chain reaction for gene expression of proinflammatory cytokines and chemokines. Synovial fluid and serum samples were collected to measure cytokine concentrations, using enzyme‐linked immunosorbent assay. Whole joints were examined histologically for the extent of synovitis and cartilage degradation, and joint tissue samples from all time points were analyzed immunohistochemically to evaluate the distribution of interleukin‐1 (IL‐1). Results Compared to C57BL/6 mice, MRL/MpJ mice had less severe intraarticular and systemic inflammation following joint injury, as evidenced by lower gene expression of tumor necrosis factor α and IL‐1β in the synovial tissue and lower protein levels of IL‐1α and IL‐1β in the synovial fluid, serum, and joint tissues. Furthermore, after joint injury, MRL/MpJ mice had lower gene expression of macrophage inflammatory proteins and macrophage‐derived chemokine (CCL22) in the synovial tissue, and also had reduced acute and late‐stage infiltration of synovial macrophages. Conclusion C57BL/6 mice exhibited higher levels of inflammation than MRL/MpJ mice, indicating that MRL/MpJ mice are protected from PTA in this model. These data thus suggest an association between joint tissue inflammation and the development and progression of PTA in mice.